2010
DOI: 10.2174/138161210792062849
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Congenital Heart Disease: The Epidemiological and Biological Link

Abstract: Cigarette smoking is a powerful human germ cell mutagen and teratogen. Congenital heart defects (CHD) is the most prevalent of all birth defects and leading cause of death in the first year of life. The purpose of this article is to review the epidemiology of the impact of cigarette smoking on CHD risk as well as to discuss the potential biological mechanisms of smoking-mediated abnormal cardiac development. Although epidemiological studies of association between parental smoking and CHD are limited, biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
1
6
1
Order By: Relevance
“…Our study confirmed that maternal smoke exposure during pregnancy is associated with an increased risk of CHDs. Moreover, the degree of the increased risk of CHDs in our study was much higher than in other studies 3 4 20 . A very local study population and relatively strict inclusion and exclusion criteria for test cases and controls used in our study, compared to other studies, likely contribute to this difference.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our study confirmed that maternal smoke exposure during pregnancy is associated with an increased risk of CHDs. Moreover, the degree of the increased risk of CHDs in our study was much higher than in other studies 3 4 20 . A very local study population and relatively strict inclusion and exclusion criteria for test cases and controls used in our study, compared to other studies, likely contribute to this difference.…”
Section: Discussioncontrasting
confidence: 82%
“…Although the mechanisms by which smoke causes CHDs have not yet been clearly elucidated, there are some clues to help us interpret these untoward effects. First, the main smoke by-products, nicotine and carbon monoxide, cross the placental barrier and induce vasoconstriction, resulting in foetal hypoxia 20 . Several animal models have indicated that chronic foetal hypoxia most likely leads to myocardial and ventricle dilation, cardiomyocyte hypertrophy, myocardial hypoplasia, and impaired foetal heart maturation due to increases in the percentage and size of binucleated cardiomyocytes that cannot be differentiated 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that smoking per se causes different types of sperm DNA damage [15], [16], [60], and paternal smoking seems independently associated with DNA adducts in embryos [19], childhood cancer in the offspring [31]–[34], [36], pregnancy loss [23], [24], lower pregnancy rate after assisted reproduction [22], non-genital birth defects [25], [26], [28][30] as well as with reduced birth weight [37]. Paternal smoking during pregnancy probably highly reflects smoking closely before conception and could thereby exert its effects through mutations or epigenetic changes in the paternal germ line by transmission to the sons.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of pregnant women in the US smoke, thereby exposing nearly 400,000 fetuses yearly to tobacco specific toxins [114]. Exposure to smoke during pregnancy has been demonstrated to increase the likelihood of congenital limb deficiencies [115], congenital heart defects [116], orofacial clefting [112], and many other developmental abnormalities. Active smoking has long been considered a teratogenic agent that increases the risk of premature birth, but recent data shows that 22%–30% of nonsmoking pregnant women exposed to SHS are also at risk [117].…”
Section: Health Outcomes and Comorbiditiesmentioning
confidence: 99%